Benchmarking risk management within the international water utility sector. Part I: Design of a capability maturity methodology. - MacGillivray, Brian H.; Sharp, J. V.; Strutt, J. E.; Hamilton, Paul D.; Pollard, Simon J. T. (Taylor & Francis, 2007)
Risk management in the water utility sector is becoming increasingly explicit. However, due to the novelty and complexity of the discipline, utilities are encountering difficulties in defining and institutionalising their risk management processes. In response, the authors have developed a sector specific capability maturity methodology for benchmarking and improving risk management. The research, conducted in consultation with water utility practitioners, has distilled risk management into a coherent, process-based framework. We identified eleven risk management processes, and eight key attributes with characterise the extent to which these processes are defined, controlled and institutionalised. Implementation of the model should enable utilities to more effectively employ their portfolio of risk analysis techniques for optimal, credible and defensible decision making.
Keywords: Maturity model; risk; analysis; management; water; sector